Sentience and salience – exploring the party politicization of animal welfare in multi-level electoral systems: Analysis of manifesto discourse in UK meso elections 1998–2017. Issue 1 (1st January 2022) - Chaney, Paul; Rees Jones, Ian; Fevre, Ralph
ABSTRACT: This study explores the party politicization of animal welfare in the context of multi-level governance in the UK. It examines over 1300 pledges in party manifestos for Scottish, Welsh and Northern Irish elections 1998–2017. It reveals the nature of party competition, including increasing salience over electoral cycles. This is complemented by examination of the party dynamics in two sub-fields: wildlife protection and farm animal welfare. The wider significance of this study lies in showing how the move to multi-level electoral politics provides new political spaces to advance animal welfare and how meso-ballots are increasingly attuned to the symbiosis of humans and animals. These factors are driving the territorialization of policy and leading to distinctive animal welfare regimes in the different countries of the UK. In addition, partisan theory reveals how the electoral politics of animal welfare varies between sub-fields and is shaped by parties' relationships with different policy communities.